Kajian Kriminologis Terhadap Tindak Pidana Korupsi Dana Desa - Purwanto, Astrid Hilarry; Latupeirissa, Julianus Edwin; Taufik, Iqbal (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2024)
Introduction: Corruption is one of the dangerous crimes that is also categorized as White Collar Crime which is a form of crime committed by a person or group who has a position using the authority they have in their work. Corruption crimes from year to year continue to increase. Purposes of the Research: to find out what are the factors that cause the crime of corruption of village funds and how to enforce the law to prevent the occurrence of corruption of village funds. Methods of the Research: The research method used in this writing is empirical juridical research. This type of research is descriptive analysis. The sources of legal materials used are primary and secondary legal materials. Techniques for collecting legal materials through literature study and then analyzing them descriptively using qualitative methods based on criminal law science Results of the Research: The results of this research are what factors cause corruption in village funds and what law enforcement efforts can be taken to prevent it from happening again. Corruption is driven by several factors, namely economic factors, poverty, and lack of awareness of the law, etc.